The Effect Of Budget Planning, Administration, Human Resources, Procurement, And Inventory Money For The Budget Absorption In Indonesia - Bandiyono, Agus; Saifuridzal, Hasan (Opción, 2019)
This study will focus on analyzing the factors that influence the absorp- tion of the Ministry of Finance’s scope of the budget, especially for goods and capital expenditure categorized as specifics commitments. This type of research is descriptive quantitative research with a survey method. Budget planning, administration, human resources, and procurement have a significant effect on the absorption of the budget within the Min- istry of Finance. The money supply does not have a significant effect on budget absorption within the Ministry of Finance. The study only used samples at the central office satker within the Ministry of Finance. Therefore, further research is expected to use a wider sample than this research for example by including the vertical office satker within the Ministry of Finance so that the results are more comprehensive.